Facilities planning - Tompkins, James A. (New York : John Wiley and Sons, 1996)
The text is devided into five parts. Part One focuses on the determination of the requirements for people, equipment, space, and material in the facility. Part Two presents concepts and techniques to facilitate the generation of alternative facilities plans. Part Three continues the focus on generation of alternative facilities plans, but concentrates on the functions of the organization. Part Four presents a variety of quantitative approaches that can be used to model specific aspects of facilities planning problems. Part Five concludes the treatment of facilities planning and includeschapters dealing with evaluation, selecting, preparing, presenting, implementing, and maintaining the facilities plan.
Keywords: Factories; Design and construction; Facility management; Facility management; Factories -- Design and construction